2018
DOI: 10.1140/epjc/s10052-018-5928-4
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic stars with conformal symmetry

Abstract: We study exact models for anisotropic gravitating stars with conformal symmetry. The gravitational potentials are related explicitly by the conformal vector. We use this relationship between the metric potentials to find new classes of exact solutions to the field equations. We identify a particular model to study the physical features and demonstrate that the model is well behaved. In particular the criteria for stability are satisfied. We regain masses, radii and surface redshifts for the compact objects PSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…(ω r = p r /ρ) and (ω t = p t /ρ) are less than 1, proving Zeldovich's condition is satisfies everywhere inside the compact object. Furthermore, in Table 1 we have shown the possible values of the physical parameters a, A and B using parameters values of the compact star SAX J1808.4-3658 with mass Table 2 shows that the central energy density is within this range, which is in complete agreement with many other reported results in the literature [45][46][47][48][49][50][51][52][53][54][55][57][58][59][60][61][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Figure 6 clearly shows that our stellar system fulfills all the energy conditions which are a basic condition for a compact astrophysical structure to be physically acceptable.…”
Section: Discussionsupporting
confidence: 86%
“…(ω r = p r /ρ) and (ω t = p t /ρ) are less than 1, proving Zeldovich's condition is satisfies everywhere inside the compact object. Furthermore, in Table 1 we have shown the possible values of the physical parameters a, A and B using parameters values of the compact star SAX J1808.4-3658 with mass Table 2 shows that the central energy density is within this range, which is in complete agreement with many other reported results in the literature [45][46][47][48][49][50][51][52][53][54][55][57][58][59][60][61][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Figure 6 clearly shows that our stellar system fulfills all the energy conditions which are a basic condition for a compact astrophysical structure to be physically acceptable.…”
Section: Discussionsupporting
confidence: 86%
“…Newton Singh et al [15] discovered electrically charged dense stars in the presence of a static conformal Killing vector. Mafa Takisa et al [16], Kileba Matondo et al [17] and Kileba Matondo et al [18] generated new stellar models with conformal symmetries with radii, masses, densities and redshifts which are consistent with observed astronomical objects. These models have been found by integrating the Einstein-Maxwell field equations for selected forms of the metric functions.…”
Section: Introductionmentioning
confidence: 78%
“…Again, we have shown that the most simple and "pedagogic" spherical matter solution -ρ = const-is very restricted and unphysical, but there has been much recent work with variable energy densities, satisfying all physical criteria, that seems to correspond to more realistic matter configurations [61,62].…”
Section: Final Remarksmentioning
confidence: 88%